1994
DOI: 10.1302/0301-620x.76b3.8175837
|View full text |Cite
|
Sign up to set email alerts
|

Nerve lesions in primary shoulder dislocations and humeral neck fractures. A prospective clinical and EMG study

Abstract: The incidence of nerve injuries in primary shoulder dislocation and humeral neck fracture is uncertain. We made a prospective study of 101 patients, using clinical examination and extensive electrophysiological assessment when there was suspicion of nerve damage. We found electrophysiological evidence of nerve injury in 45%, most involving the axillary, suprascapular, radial and musculocutaneous nerves. There were significantly more nerve injuries in older patients and those with a haematoma. Most patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
0
14

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(108 citation statements)
references
References 0 publications
6
88
0
14
Order By: Relevance
“…However, injuries resulting from shoulder dislocation affect predominantly the infraclavicular part of the plexus at the level of cords and nerves, often extending up to retropectoralis minor space [11,65,66]. It may be explained by the fact that trauma in abduction causes primarily injury to the lower part of the brachial plexus [64].…”
Section: Affection Of Particular Nervesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, injuries resulting from shoulder dislocation affect predominantly the infraclavicular part of the plexus at the level of cords and nerves, often extending up to retropectoralis minor space [11,65,66]. It may be explained by the fact that trauma in abduction causes primarily injury to the lower part of the brachial plexus [64].…”
Section: Affection Of Particular Nervesmentioning
confidence: 99%
“…Shoulder dislocation most commonly causes injury to the axillary nerve, both when single nerve injury is considered and in combination with other nerves [5,11,16,18,42]. Axillary nerve was found to be affected in all patients with neurologic deficit after shoulder dislocation (100%) in several studies [6,7,22,23,51,[67][68][69][70], and in all analysed studies but two (Hems and Mahmood, Stenning et al), it occupied the first place among injuries to the long nerves of the brachial plexus [18,54].…”
Section: Affection Of Particular Nervesmentioning
confidence: 99%
“…4,23 The prevalence of electrophysiologically documented nerve damage associated with closed shoulder trauma is reported to be up to 62% and most frequently involves the axillary nerve. 10 Occasionally, the axillary nerve is damaged during reduction of a shoulder dislocation. After glenohumeral dislocation, transient axillary numbness is often noted.…”
Section: Mechanism Of Injurymentioning
confidence: 99%
“…The axillary nerve is reportedly the most susceptible to injury after fractures with and without dislocation of the proximal humerus [27]. Several studies have reported using nerve monitoring in the asessment of proximal humerus fractures [6,28,30]. de Laat et al found electrophysiologic evidence of nerve injury in 45% of cases (n = 101) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported using nerve monitoring in the asessment of proximal humerus fractures [6,28,30]. de Laat et al found electrophysiologic evidence of nerve injury in 45% of cases (n = 101) [6]. Visser et al reported axonal nerve lesions in proximal humeral fractures were much more common than has been reported in the literature: EMGs showed axonal denervation in 67% (96 of 143) of the patients and solitary nerve injury was seen in 21 of 143 cases [30].…”
Section: Introductionmentioning
confidence: 99%